Anti-inflammatory and Anti-oxidant Activity of Hidrox® in Rotenone-Induced Parkinson's Disease in Mice - Rosalba Siracusa; Maria Scuto; Roberta Fusco; Angela Trovato; Maria Laura Ontario; Roberto Crea; Rosanna Di Paola; Salvatore Cuzzocrea; Vittorio Calabrese (MDPI AG, 2020)
Background: In developed countries, the extension of human life is increasingly accompanied by a progressive increase in neurodegenerative diseases, most of which do not yet have effective therapy but only symptomatic treatments. In recent years, plant polyphenols have aroused considerable interest in the scientific community. The mechanisms currently hypothesized for the pathogenesis of Parkinson's disease (PD) are neuroinflammation, oxidative stress and apoptosis. Hydroxytyrosol (HT), the main component of Hidrox® (HD), has been shown to have some of the highest free radical evacuation and anti-inflammatory activities. Here we wanted to study the role of HD on the neurobiological and behavioral alterations induced by rotenone. Methods: A study was conducted in which mice received HD (10 mg/kg, i.p.) concomitantly with rotenone (5 mg/kg, o.s.) for 28 days. Results: Locomotor activity, catalepsy, histological damage and several characteristic markers of the PD, such as the dopamine transporter (DAT) content, tyrosine hydroxylase (TH) and accumulation of α-synuclein, have been evaluated. Moreover, we observed the effects of HD on oxidative stress, neuroinflammation, apoptosis and inflammasomes. Taken together, the results obtained highlight HD's ability to reduce the loss of dopaminergic neurons and the damage associated with it by counteracting the three main mechanisms of PD pathogenesis. Conclusion: HD is subject to fewer regulations than traditional drugs to improve patients' brain health and could represent a promising nutraceutical choice to prevent PD.